Provincial Funding of Postsecondary Education Under The Established Programs Financing - Wu, Terry Yuk Shing (Canadian Journal of Higher Education, 1985)
This study reviews the provincial funding of postsecondary education under the Established Programs Financing (EPF) arrangements introduced in 1977. Since 1977, federal transfers to the provinces for financing postsecondary education have increased in line with the growth rate of nominal gross national product, rather than in line with operating costs. Because the federal transfers were unconditional grants, the provinces were not obliged to spend the postsecondary transfers on higher education. Consequently, the block grant under EPF has led to provincial spending restraint on postsecondary education.